MITIGASI RESIKO SUKUK GAGAL BAYAR DALAM PERPEKTIF EKONOMI SYARIAH - Imam Mawardi; Moch. Su'eb; A. Afif Amrullah; Nihro Afandi; Uswatun Chasanah (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2024)
The Islamic finance industry has grown rapidly in global financial markets until 2015 when it experienced a slowdown in 2016 with an estimated value of USD 1.89 trillion. Defaults on sukuk must be able to be overcome or avoided, so through this paper we want to reveal the risks that can arise from sukuk and mitigate the risk of sukuk defaulting. The type of research method used in this research is literature, namely research whose object discovery is carried out by digging literature information. The result of this study, the resolution of the risk of default is one of them by restructuring the sukuk. As for restructuring, namely rescheduling, providing an extension of time, regulations must be tightened, such as conventional bonds continue to use sharia principles at the same time and all Sukuk transactions must be halal, avoid transactions of riba (paying and taking interest), gharar (ambiguity, fraud), and maysir (games of chance), prohibition of investing in products and services that are not in accordance with sharia, need approval from the Advisory Board Sharia. There are two major implications of this sharia principle of dispute resolution. First, the parties are given the discretion to determine resolutions through fair negotiations, as long as they do not conflict with other Sharia rules, such as usury, gharar, and maysir. Second, there is less concrete scaffolding for debt restructuring because the parties can work out a number of solutions.